Longitudinal cohort survey of women's smoking behaviour and attitudes in pregnancy: study methods and baseline data - Orton, Sophie; Bowker, Katharine; Cooper, Sue; Naughton, Felix; Ussher, Michael; Pickett, Kate E.; Leonardi-Bee, Jo; Sutton, Stephen; Dhalwani, Nafeesa N.; Coleman, Tim (BMJ Publishing Group, 2014)
Objectives: To report methods used to assemble a contemporary pregnancy cohort for investigating influences on smoking behaviour before, during and after pregnancy and to report characteristics of women recruited.